Sports teams' home market size in the digital age: Analyzing social media drawing power - Philipp Kunz-Kaltenhäuser (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2023)
The sport economic literature relies on the city size to proxy for the size of the home market of sports teams. This paper seeks to clarify whether the commonly used definition for home market size in sports economics is actually a valid measure for revenue potential in the modern digital age. Specifically, in this empirical exercise the interest is to investigate to what extent social media following is adding to our understanding of home markets. In doing so, it closely connects to the literature on outcome uncertainty, by considering the compounded season uncertainty for home games, and the literature on superstars in sport as a determinant for demand. The econometric analysis uses NFL stadium attendance data between 2009 and 2019 to examine the question of the relationship of social media and stadium attendance. It applies censored tobit models to estimate the effects. The results suggest a significant relationship between social media following and stadium attendance, even when controlling for the metropolitan area where the stadium is located. It argues that our commonly used definition of home market size is built on the outdated concept of localized markets and should be revisited.
Keywords: Z20; L83; D47; 330; home markets; national football league; social media; uncertainty of outcome; franchise reallocation; econometrics